Analisis Konseptual tentang Penerapan Sati (Mindfulness) dalam Pendidikan untuk Menangani Quarter-Life Crisis pada Mahasiswa - Andika Febrianto; Hadi Wijaya Halim (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
The application of mindfulness (sati) in education is becoming increasingly relevant, particularly in addressing the psychological challenges faced by students in the modern era. One such challenge is the quarter-life crisis, a period of identity and life direction crisis common among individuals aged 18 to 30. This crisis is characterized by psychological distress, anxiety about the future, uncertainty in careers and social relationships, and a decline in emotional well-being. This research aims to analyze how mindfulness practices can be implemented as a strategic approach to help students manage stress, increase self-awareness, and strengthen overall mental health. The method used in this research is a qualitative study through a literature review of scientific journals, research reports, and analysis of various mindfulness programs implemented in higher education settings, both domestically and internationally. The results indicate that consistent application of mindfulness can help students recognize emotions, reduce anxiety levels, improve learning focus, and build emotional resilience in the face of academic and social pressures. Furthermore, the integration of mindfulness practices into the curriculum and daily campus activities is considered to create a more supportive and reflective learning environment. The implications of this study emphasize the importance of higher education institutions providing space and support for the development of mindfulness programs as part of character education and mental health. Further research is recommended to assess the long-term effectiveness of mindfulness interventions, as well as adapt training models to suit the cultural context and needs of Indonesian students.